Comparison of high-level athlete training between Chinese and American universities based on the internet of things - Zhu, X. (Revista Brasileira de Medicina do Esporte, 2021)
In order to improve the training quality of high-level athletes in Chinese and American universities, an athlete`s sports information transmission model is designed based on the Internet of Things (IoT). The communication protocol between Ayla module and the main motion control board, Ayla module and client APP or cloud platform, and APP and cloud platform in the system is designed in detail. For the Ayla module, the most important hardware part of the system, the internal composition and software design are described. In the mobile phone client part that is closely related to the user, the MVC architecture is adopted, the singleton and agent design patterns are utilized, and the functional design of each part is elaborated, including APP interface animation, data transmission format, network communication, and database storage. The research results show that the system of this study can handle most of the athlete training information, and the prediction accuracy exceeds the traditional algorithm. This research study is of great significance for improving the training efficiency of high-level athletes and further expanding the scope of application of the IoT.